1991
DOI: 10.1295/polymj.23.103
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Depolarization Study on Local Motions of Anthracene-Labeled Poly(alkyl methacrylate)s in Dilute Solutions and Evaluation of Their Chain Stiffness

Abstract: ABSTRACT:Samples of Poly(methyl methacrylate) (PMMA), poly(ethyl methacrylate) (PEMA), and poly(isopropyl methacrylate) (PiPMA) labeled with anthracene in the middle of the backbone chain were synthesized, and their local motions in dilute solutions were investigated by the fluorescence depolarization technique. Both the static stiffness parameter s-[ and the mean relaxation time T m as a measure of the dynamic chain stiffness were evaluated from the time-resolved data of fluorescence anisotropy ratio, and a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 29 publications
(25 reference statements)
0
17
0
Order By: Relevance
“…38 It has been revealed that dynamic stiffness (segmental relaxation time) increases generally as static chain stiffness increases in dilute solutions. 39,40 Figure 5 shows the WAXS profiles for the present PS derivatives. It is known that polystyrene exhibits two dominant halos at around s = 7.1 and 13.5 nm -1 [s = (4π/λ) sin θ].…”
Section: Resultsmentioning
confidence: 99%
“…38 It has been revealed that dynamic stiffness (segmental relaxation time) increases generally as static chain stiffness increases in dilute solutions. 39,40 Figure 5 shows the WAXS profiles for the present PS derivatives. It is known that polystyrene exhibits two dominant halos at around s = 7.1 and 13.5 nm -1 [s = (4π/λ) sin θ].…”
Section: Resultsmentioning
confidence: 99%
“…The relaxation time became longer in the order of poly (ethyl methacrylate) ( ), poly(methyl methacrylate) (PMMA), and poly (iso-propyl methacrylate) (PiPMA). 18 The dynamic chain stiffness showed a parallel relationship with the static chain stiffness, and the chain stiffness depended on both the bulkiness of the alkyl residue and the chain tacticity (racemo fraction). For the local motion of the polystyrenes, the activation energy was larger in poor solvents than in good solvents.…”
Section: Introductionmentioning
confidence: 95%
“…( 1)-(3). Since the time constant of the micro-Brownian motion in the polymer chain leading to the local conformation change is reported to be of the order of sub-nanoseconds-nanoseconds in the solution phase, [32][33][34][35] the present value of k DM suggests that the dimer cation formation was actually accompanied by a local geometrical change to result in a favorable conformation of the dimer cation. Summarizing the above results and discussion, it is concluded that the electron transfer dynamic behaviors of the PVPy-TCNB system in chloroform solution is represented not by the simple model based on Scheme 1 but by the biexponential decay process shown in Scheme 2.…”
Section: Photoinduced Electron Transfer Dynamics In Chloroform Solutionmentioning
confidence: 99%